Sigma-1 Receptor Expression in Sensory Neurons and the Effect of Painful Peripheral Nerve Injury. (10th September 2013) - Bangaru, Madhavi L; Weihrauch, Dorothee; Tang, Qing-Bo; Zoga, Vasiliki; Hogan, Quinn; Wu, Hsiang-en
Background: The sigma-1 receptor (σ1R), an endoplasmic reticulum chaperone protein, is widely distributed and regulates numerous intracellular processes in neurons. Nerve injury alters the structure and function of axotomized dorsal root ganglion (DRG) neurons, contributing to the development of pain. The σ1R is enriched in the spinal cord and modulates pain after peripheral nerve injury. However, σ1R expression in the DRG has not been studied. We therefore characterized σ1R expression in DRGs at baseline and following spinal nerve ligation (SNL) in rats. Results: Immunohistochemical (IHC) studies in DRG sections show σ1R in both neuronal somata and satellite glial cells. The punctate distribution of σ1R in the neuronal cytoplasm suggests expression in the endoplasmic reticulum. When classified by neuronal size, large neurons (>1300 μm) showed higher levels of σ1R staining than other groups (700–1300 μm, <700 μm). Comparing σ1R expression in neuronal groups characterized by expression of calcitonin gene-related peptide (CGRP), isolectin-B4 (IB4) and neurofilament-200 (NF-200), we found σ1R expression in all three neuronal subpopulations, with highest levels of σ1R expression in the NF-200 group. After SNL, lysates from L5 DRGs that contains axotomized neurons showed decreased σ1R protein but unaffected transcript level, compared with Control DRGs. IHC images also showed decreased σ1R protein expression, in SNL L5 DRGs, and to a lesser extent in the neighboring SNL L4 DRGs. Neurons labeled by CGRP and NF-200 showed decreased σ1R expression in L5 and, to a lesser extent, L4 DRGs. In IB4-labeled neurons, σ1R expression decreased only in axotomized L5 DRGs. Satellite cells also showed decreased σ1R expression in L5 DRGs after SNL. Conclusions: Our data show that σ1R is present in both sensory neurons and satellite cells in rat DRGs. Expression of σ1R is down-regulated in axotomized neurons as well as in their accompanying satellite glial cells, while neighboring uninjured neurons show a lesser down-regulation. Therefore, elevated σ1R expression in neuropathic pain is not an explanation for pain relief after σ1R blockade. This implies that increased levels of endogenous σ1R agonists may play a role, and diminished neuroprotection from loss of glial σ1R may be a contributing factor.